2019
DOI: 10.1093/jas/skz100
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Effects of age and confinement on pupillary light reflex in sows1

Abstract: Pupillary reflex has been used as a method to examine psychological problems in human clinics and mental disease research. Intensive animal farming has been shown to lead to chronic stress resulting in depression; however, comparing with humans we lack an effective clinical method to clinically inspect these psychological problems in animals. The goal of this study was to investigate the effect of age and housing conditions (confined crates vs. group pens) on pupillary light reflex (PLR) of sows to explore whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Some studies have documented that long-term restraint in intensive sow production develops various types of depressive symptoms such as stereotypic behavior, decreased sucrose preference, and pupil rigidity ( 18 , 19 ). However, few have explored the pathogenesis and mechanisms of depression in pigs using animal models of depression induced by acute or chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have documented that long-term restraint in intensive sow production develops various types of depressive symptoms such as stereotypic behavior, decreased sucrose preference, and pupil rigidity ( 18 , 19 ). However, few have explored the pathogenesis and mechanisms of depression in pigs using animal models of depression induced by acute or chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…When animals are exposed to situations that they cannot control or are unpredictable (such as isolation, acute noise, or confinement) [30], adaptive hypothalamic, sympathetic, immune, and behavioral responses serve to survive [31]. In farm animals, routine situations such as handling, restraining, or transport are events that can induce states of anxiety, distress, depression, or fear [32,33]. Fear is a negative, subjective, and emotional experience derived from the recognition or anticipation of actual danger [34].…”
Section: Stressors Of Psychological Originmentioning
confidence: 99%
“…Compared with group-housed sows, the PLR latencies and duration of stall-housed sows were longer [14]. Additionally, the PLR of sows is affected by age [18]. Our colleague previously found that there were differences in the psychophysiological states of sows with different PLRs and the differences increased with the increase in parity [19].…”
Section: Introductionmentioning
confidence: 99%